The Rsal Polymorphism in the α-Fibrinogen Gene and Response of Plasma Fibrinogen to Physical Training - Rauramaa, Rainer; Väisänen, Sari B.; Kuhanen, Raimo; Penttilä, Ilkka; Bouchard, Claude (Thrombosis and Haemostasis, 2000)
We have previously reported cross-sectional data on an interaction effect between physical activity and α-fibrinogen Rsal polymorphism on fibrinogen in postmenopausal women. In the present controlled randomised study, we investigated the role of the Rsal polymorphism in determining the response of fibrinogen to long-term regular exercise. Middle-aged men (n = 140), randomly selected from the population registry, were randomised into an exercise or a reference group for a 3-year low intensity exercise intervention. Complete data were available in 125 men. The Rsal restriction enzyme detects threonine (Thr) to alanine change in the fibrinogen α codon 312. Anaerobic ventilatory threshold increased by 4%, but decreased by 2% in the exercise and reference groups, respectively. Mean fibrinogen did not decrease in either study group. However, in the exercise group, individual changes in anaerobic threshold explained 48% of the variance in fibrinogen changes in the Thr homozygotes. Our data offer a new aspect of beneficial effects of regular physical exercise on risk factors for coronary heart disease.
Keywords: Fibrinogen; DNA polymorphism; physical exercise training; randomised clinical trial; population based study